2006
DOI: 10.1103/physrevlett.97.118103
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic to Nematic Liquid Crystalline Phase Transition ofF-Actin Varies from Continuous to First Order

Abstract: We report that the properties of the isotropic to nematic liquid crystalline phase transition of F-actin depend critically on the average filament length. For average filament lengths longer than 2 microm, we confirm previous findings that the phase transition is continuous in both alignment and concentration. For average filament lengths shorter than 2 microm, we show for the first time a first order transition with a clear discontinuity in both alignment and concentration. Tactoidal droplets of coexisting is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 30 publications
(47 reference statements)
5
36
0
Order By: Relevance
“…2b), indicating its properties as a nematic liquid crystal. It has already been shown that F-actin forms a nematic phase at high concentrations 15,[27][28][29] . From observations in the bulk solution, it has been reported that the nematic liquid crystallization of F-actin depends on its concentration and length like many other rod-like molecules, and the liquid crystal phase tends to appear at 50 μM or higher concentrations of F-actin 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…2b), indicating its properties as a nematic liquid crystal. It has already been shown that F-actin forms a nematic phase at high concentrations 15,[27][28][29] . From observations in the bulk solution, it has been reported that the nematic liquid crystallization of F-actin depends on its concentration and length like many other rod-like molecules, and the liquid crystal phase tends to appear at 50 μM or higher concentrations of F-actin 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…This actin concentration (3.75 mg/ml) is much lower than the measured isotropic-nematic (I-N) transition concentration (> 7 mg/ml) for 1 µm F-actin under similar ionic conditions [14]. SAXS experiments were performed both at 9KeV at BL4-2 of the Stanford Synchrotron Radiation Laboratory and at 12KeV the BESSRC-CAT (BL12-ID) at the Advanced Photon Source.…”
mentioning
confidence: 84%
“…On the other hand, numerous experimental and numerical studies have been recently devoted to the analysis of equilibrium properties in systems of non-spherical particles [18,19,20,21,22,23,24,25,26]. Of special interest are those studies dealing with lattice versions of the present problem, where the situation is much less clear than in the continuum case.…”
Section: Introductionmentioning
confidence: 99%